Defining metabolic activity of nephrolithiasis – Appropriate evaluation and follow-up of stone formers - Daniel A. Wollin; Adam G. Kaplan; Glenn M. Preminger; Pietro Manuel Ferraro; Antonio Nouvenne; Andrea Tasca; Emanuele Croppi; Giovanni Gambaro; Ita P. Heilberg (Asian Journal of Urology)
Considering the variation in metabolic evaluation and medical management of kidney stone disease, this consensus review was created to discuss the metabolic activity of nephrolithiasis, define the difference between single and recurrent stone formers, and develop a schema for metabolic and radiologic follow-up. A systematic review of the literature was performed to identify studies of metabolic evaluation and follow-up of patients with nephrolithiasis. Both single and recurrent stone formers share many similarities in metabolic profiles. The study group determined that based on an assessment of risk for stone recurrence and metabolic activity, single and recurrent stone formers should be evaluated comprehensively, including two 24 h urine studies on a random diet. Targeted medication and dietary recommendations are effective for many patients in reducing the risk of stone recurrence. Follow-up of those with stone disease should be obtained depending on the level of metabolic activity of the patient, the risk of chronic kidney disease and the risk of osteoporosis/osteopenia. A standard scheme includes a baseline metabolic profile, a repeat study 3–6 months after initiation of treatment, and then yearly when stable, with abdominal imaging obtained every 1–2 years. Keywords: Follow-up, Medical management, Metabolic evaluation, Urolithiasis